Evaluation of Medicolegal Geriatric Deaths Between 2005-2009 in Denizli Turkey - Kurtuluş, Ayşe; Acar, Kemalettin; Boz, Bora; Cenger, Cüneyt Destan (The Bulletin of Legal Medicine, 2010)
Aging is a continuous and universal process seen in all creatures which causes decrease in all functions. According to World Health Organisation the start of geriatric period is 65 years of age. Evaluating geriatric deaths help society to determine health precedences. In this study, medico-legal geriatric death cases between the years 2005 and 2009 in Denizli territory were examined retrospectively. All of the cases were analyzed with regard to gender, age, cause of death, origin of death and place of death. The autopsy records of Forensic Medicine Department of Pamukkale University Medical Faculty were used. Geriatric deaths constituted 18.95% (251 cases) of all the medicolegal autopsy cases (1324) in this five years period. One-hundredseventyfive of them were male and 76 were female. Average of ages was 74,75 + 6,63. It was seen that accidental deaths were the most common way of the medicolegal cases which was followed by natural deaths. In natural deaths, cardiovascular diseases were the most often cause of death. It is understood that medicolegal autopsies taken place in right conditions and done absolutely by a forensic medicine profession can provide a lot of data about elder deaths. With these datas, determination of causes and origins of death can help the removal of avoidable reasons. Key words: Old age, causes of death, forensic medicine